An Environmental Escherichia coli Strain Is Naturally Competent to Acquire Exogenous DNA - Riva, Francesco; Riva, Valentina; Eckert, Ester M.; Colinas, Noemi; Di Cesare, Andrea; Borin, Sara; Mapelli, Francesca; Crotti, Elena (Frontiers in Microbiology, 2020)
The diffusion of antibiotic resistance determinants in different environments, e.g., soil and water, has become a public concern for global health and food safety and many efforts are currently devoted to clarify this complex ecological and evolutionary issue. Horizontal gene transfer (HGT) has an important role in the spread of antibiotic resistance genes (ARGs). However, among the different HGT mechanisms, the capacity of environmental bacteria to acquire naked exogenous DNA by natural competence is still poorly investigated. This study aimed to characterize the ability of the environmental Escherichia coli strain ED1, isolated from the crustacean Daphnia sp., to acquire exogenous DNA by natural competence. Transformation experiments were carried out varying different parameters, i.e., cell growth phase, amount of exogenous DNA and exposition to artificial lake water (ALW) and treated wastewater to mimic environmental-like conditions that may be encountered in the agri-food system. Results were compared with those showed by the laboratory E. coli strain DH5α. Our experimental data, supported by genomic sequencing, showed that, when exposed to pure water, ED1 strain was able to acquire exogenous DNA with frequencies (10–8–10–9) statistically higher than the ones observed for DH5α strain (10–10). Interestingly, higher values were retrieved for ED1 than DH5α strains exposed to ALW (10–7 vs. 10–9, respectively) or treated wastewater (10–8 vs. 10–10, respectively). We tested, therefore, ED1 strain ability to colonize the rhizosphere of lettuce, a model plant representative of raw-consumed vegetables of high economic importance in the ready-to-eat food industry. Results showed that ED1 strain was able to efficiently colonize lettuce rhizosphere, revealing a stable colonization for 14 days-long period. In conclusion, ED1 strain ability to acquire exogenous DNA in environmental-like conditions by natural competence, combined with its ability to efficiently and stably colonize plant rhizosphere, poses the attention to food and human safety showing a possible route of diffusion of antibiotic resistance in the agri-food system, sustaining the “One Health” warnings related to the antibiotic spread.